STRATEGI INOVASI MENGATASI KREDIT BERMASALAH PADA USAHA EKONOMI KELURAHAN SIMPAN PINJAM (UEK-SP) LABUH BARU TIMUR (LBT) SEJAHTERA KOTA PEKANBARU - Khanaro, Barandear; Nas, Syakdanur; Rosyetti, Rosyetti (Jurnal Tepak Manajemen Bisnis, 2018)
This research conducted on Economic Business Urban VillageSavings-Loans (UEK-SP) and The purpose of this research was to analyze whatfactors cause loan arrears (problem loans) in UEK-SP LBT Sejahtera andformulate a strategy that able to overcome the problem loans.This research uses a qualitative method. Research location in UEK-SP LBTSejahtera. Determination of the sample using census method with all members ofthe population as the subject studied were as many as 67 sources. Methods of datacollection in this study include questionnaires, interviews, and observation. Dataanalysis method used was SWOT.The result of the research shows that the factors that cause problem loans inUEK-SP LBT Sejahtera were guidance, monitoring and evaluation to the lesserbeneficiaries, and strategies that able to overcome problem loans at UEK-SP LBTSejahtera by optimizing the guidance and supervision to the user , legal experts tobe added, and visit the benefactor directly when it starts to happen late pay.